Pelatihan dan Pendampingan PIRT Produk Rengginang Pada Kelompok Ulva Lestari di Desa Duwet Situbondo - Nurul Amalia Silviyanti Siswoyo; Ani Listriyana; Gema Iftitah AY; Vina Vina dzurrotoon nafisah; Rifkian jorgi wardana (Jurnal Insan Pengabdian Indonesia, 2023)
Duwet Village is one of the areas on the coast of Situbondo where most of the people are fishermen and seafood craftsmen like the partners in this service who are makers of processed seafood, namely rengginang. This UMKM does not have a P-IRT because  do not understand the importance of P-IRT in the food business. The aim of this service is to provide training on the importance of P-IRT to small food UMKM in Duwet Village, Panarukan District, Situbondo. Apart from that, the team will also accompany to apply for P-IRT from the start of the application until the permit is issued. The method used in implementing this service is socializing the importance of P-IRT, training on how to apply for P-IRT and mentoring. This service was attended by 20 people, where the members who came took part in the training enthusiastically. The participants who attended finally understood the importance of P-IRT permits for home industries like the one they are currently implementing. The training continued with assistance with the P-IRT permit for one of the group members, whose permit was finally issued two months after the application